Justyna Dargel (1860-1926) - from the History of Warmińska Sect - Zawadzki, Wojciech (Studia Warmińskie, 2011)
In the second half of nineteenth century, in the warmińska diocese, arose a new sect, inspired by Maria’s flashes of insight in Gietrzwałd. The sect was estabilished by Justyna Dargel. It found a protector in a person of warmiński priest, Michał Reddig. The sect was assembling a group of laic people, mostly from the area of Warmia. Warmińscy bishops were trying, unsuccessfully, to eliminate the threat of the division in Warmiński Church. Critical, proved to be the departure of Dargel, Redding and their followers to Trieste, former Austria. There, the sect suffered the marginalization and the decay.